An Empirical Analysis of the Stepwise Combinatorial Models of Taxes and the Effects on Total Collected Revenue in Nigeria - Adebayo, Adebayo Gabriel (International Journal For Research In Business, Management And Accounting, 2017)
Much had been discussed, debated and researched on the contribution of the contemporary tax system in Nigeria to public finance, using the total collected revenue (TCR) of the Federal Government as a proxy. That the petroleum profit tax (PPT) have been contributing to the TCR is outside any controversial status and was the only sustainable tax revenue representing a high proportion of the TCR of the Federal Government at least for the past two decades.. Value added tax (VAT) also started on a very encouraging springboard, generating revenue more than budgeted at commencement and still proving its worth. The company income tax (CIT) and customs and excise (CEX) taxes are also important in the study of the Nigerian tax system. This study aims at verifying whether VAT, CIT, PPT, and CEX as independent variables actually contributed to the dependent variable TCR. Ordinary Least Square OLS) was used to evaluate 15 stepwise combinatorial models. In the final analysis of the 15 models, findings revealed that each variable appeared 8 times. The PPT was significant in all the models i.e. 8 times out of 8 times (100%) and ranked first.. The remaining three taxes were each significant 4 out of 8 times implying 50% performance for each. All the independent variables pooled together 62.5 percent significance. It was recommended that government should expand tax bases on VAT rather than increasing its rate, and reduce CIT rate of 30 percent to reduce tax evasion and also to minimize do or die tax avoidance strategies.